Adsorption of Reactive Red Dye using regenated activated carbon : batch and column studies - Mohamad Fikri Bin Abas (School of Environmental Engineering University Malaysia Perlis, 2011)
Reactive azo dyes, such as reactive Red 120 are commonly use in textile industry. Low utilization degree and its functional group bonds to water is a problem for the removal from wastewater. Granular activated carbon (GAC) used to adsorb reactive dye. It has limited adsorption ability. After some period, the GAC become exhaused and disposed. the exhaused GAC replaced by new GAC for as a result. Regeneration of activated carbon, method to reactivate carbon adsorption capacity using chemical and thermal (pyrolysis) treatment. Purpose on this work is to compare the efficiency of adsorption by activated carbon ; fresh , spent, chemical and thermal regeneration towards reactive dye. Batch and column studies were conducted to investigate the performance of the activated carbons.